Menyalurkan Zakat untuk Sekolah dan Pesantren perspektif Syaikh Abdul Wahhab Al-Sya’rani dan Syekh Mahmud Syaltut - Bastoni, Ahmad; Hidayatullah , Erik; Rohman, Muhammad Taufiqur (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2022)
Abstract: This article examines the law on distributing Zakat to schools and Islamic boarding schools from the perspective of Syaikh Abdul Wahhab al-Sya'rani and Syaikh Mahmud Syaltut. This article results from library research, which is descriptive and analytical using a comparative approach method. The data sources for this research are books by Shaykh Abdul Wahab al-Sya'rani and works by Mahmud Syaltut. Using documentation data processing techniques, the data is organized, edited and analyzed using an inductive mindset. The results of the research reached two conclusions. First, Shaykh Abdul Wahab Sya'rani agrees with the four schools of thought (Hanafi, Maliki, Syafi'i and Hambali), namely stating that it is not permissible to distribute Zakat to other than those mentioned by Allah in His word QS. At-Taubah, 9: (60). Zakat may not be distributed to build mosques, bridges, etc. The target does not have ownership rights regarding Zakat, even though it is a pious charity. The sentence innamā in that verse becomes a barrier to other than the eight groups that Allah has determined. Second, according to Syaikh Mahmud Syaltut, mosque financing is included in zakat expenditure as stated in the QS. At-Taubah, 9: (60) with the name sabilillah. In the current context, this opinion aligns with the idea of Al-Azhar cleric and reformer Sayid Muhammad Rasyid Ridha, who interpreted the meaning of sabilillah as unlimited groups of zakat recipients. Keywords: Zakat law, schools and Islamic boarding schools, comparative analysis, Syaikh Abdul Wahab al-Sya'rani, and Syaikh Mahmud Syaltut. Abstrak: Artikel ini mengkaji hukum menyalurkan zakat untuk sekolah dan pesantren perspektif Syaikh Abdul Wahhab al-Sya’rani dan Syekh Mahmud Syaltut. Tulisan ini adalah hasil penelitian pustaka (library research) yang bersifat deskriptif analitis dengan menggunakan metode pendekatan komparatif. Sumber data penelitian ini adalah kitab karya Syaikh Abdul Wahab al-Sya’rani dan karya Mahmud Syaltut. Dengan teknik pengolahan data dokumentasi data kemudian diatur, disunting, dan dianalisis dengan pola pikir induktif. Hasil penelitian mendapatkan dua kesimpulan. Pertama, Syaikh Abdul Wahab Sya’rani sependapat dengan mazhab empat (Hanafi, Maliki, Syafi’i dan Hambali), yaitu menyatakan tidak bolehnya mendistribusikan zakat kepada selain yang disebutkan Allah dalam firman-Nya QS. At-Taubah, 9: (60). Zakat tidak boleh didistribusikan untuk membangun masjid, jembatan dan lain sebagainya. Alasannya adalah, sasaran tersebut tidak memiliki hak kepemilikan dalam hal zakat, walaupun berfungsi sebagai amal soleh. kalimat innamā dalam ayat itu menjadi pembatas terhadap selain delapan golongan yang telah ditentukan Allah. Kedua, menurut Syaikh Mahmud Syaltut, pembiayaan masjid termasuk dalam pembelanjaan zakat sebagaimana dinyatakan dalam QS. At-Taubah, 9: (60) dengan nama sabilillah. Pendapat ini, dalam konteks masa kini sejalan dengan pendapat ulama Al-Azhar dan tokoh pembaharu Sayid Muhammad Rasyid Ridha yang memaknai pengertian sabilillah dengan golongan penerima zakat tidak terbatas. Kata kunci: Hukum zakat, sekolah, dan pesantren, analisis komparatif, Syaikh Abdul Wahab al-Sya’rani, dan Syaikh Mahmud Syaltut